Mathematical ability of Bugis community in designing Lipa' Sabbe of Sengkang - Zulfiqar Busrah; Andi Aras; Buhaerah Buhaerah; Hikmawati Pathuddin (Journal of Research and Advances in Mathematics Education)
This research is an ethnomathematical research that aims to explore the mathematical abilities of the Bugis people in weaving the lipa’ sabbe. This study applies a qualitative method with an ethnographic approach. The data were collected through observation, interviews, and documentation. Based on the results, it can be explained that in the process of weaving silk, the craftsmen combine the techniques of counting, designing, placing, and measuring as mathematical activity to produce various motifs. The weaver's ability to count and design motifs produces geometric planes that are transformed through a combination of reflection, translation, and dilatation. In making visualized motifs resembling curved planes such as the lagosi motif, the phinisi or the batumesang motif, they are approximated by using a collection of rectangular pixels from the arrangement of warp, weft  and other motif yarns such as gold or viscose. The redesign of the silk motif uses the the number patterns identified on the arrangement of the yarns. In algebra, the lipa’ sabbe motif can be represented by a set of constant functions, parallel linear functions, or degree-n polynomial. The results of this study indicate that the mathematical concepts in lipa’ sabbe motifs are not only in the form of geometric concepts, but also include the concepts of number pattern, and algebra. Based on the manufacturing process and the resulting motifs indicate that the craftsmen have uniq mathematical abilities.